The Cuban Missile Crisis: Leadership as Disturbance, Informed by History. Issue 2 (15th September 2015) - Chace, Sarah
Abstract: The Cuban missile crisis of October 1962 cannot be over‐studied for the lessons it teaches about leadership. As documents have become declassified, it has now become known that President Kennedy and his team of advisors considered the crisis from multiple angles, ranging from a traditional response to perceived aggression to transactional leadership—in this case, secretly trading the removal of Soviet missiles in Cuba for the removal of American missiles in Turkey. The resolution of the Cuban missile crisis involved more than transactional leadership, however. In the complex negotiations that followed the discovery of the missiles, President Kennedy and his team of advisors experienced an evolution in their thinking, while operating under intense strain. The conceptual frameworks that best describe Kennedy's leadership in this context are Voegelin's notion of historical consciousness and Heifetz's conceptions of adaptive leadership.